Are radicalization and terrorism associated with psychiatric disorders? A systematic review. (September 2021) - Trimbur, Margot; Amad, Ali; Horn, Mathilde; Thomas, Pierre; Fovet, Thomas
Abstract: Background: The risk factors for radicalization and terrorism represent a key research issue. While numerous data on the sociological, political, and criminological profiles of radicalized people and terrorists are available, knowledge about psychiatric disorders among these populations remains scarce and contradictory. Method: We conducted a systematic review of the literature regarding psychiatric disorders among both radicalized and terrorist populations. Results: We screened 2, 856 records and included a total of 25 articles to generate a complete overview. The vast majority of studies were of poor methodological quality. We assessed three population groups: people at risk of radicalization, radicalized populations, and terrorist populations. The results showed important variations in the prevalence rates of psychiatric disorders depending on the study population and methodology. People at risk of radicalization have been reported to have depressive disorders, but contradictory findings exist. Psychiatric disorders range from 6% to 41% in the radicalized population and from 3.4% to 48.5% among terrorists. Among terrorists, psychiatric disorders are more frequent for lone-actor terrorists than for those in groups. Conclusion: We were not able to identify a significant association between radicalization, terrorism, and psychiatric disorders in our systematic review. However, some research suggests high rates of psychiatric disorders in subgroups of radicalized people and lone-actor terrorists. Further studies using standardized psychiatric assessment methods are urgently needed.